Afghanistan in 2024: Muddling Through?. Issue 1 (20th November 2014) - Kilcullen, David
This paper highlights trends in Afghan security and development, including capacities of Taliban and Al Qaeda insurgencies, national forces' casualty and desertion rates, and citizen rage spurred by abusive authorities, profiteering elites and ethnic leaders. In coming years, the unity central government may fall apart. As in Pakistan, U.S. targeted killings by drones and raids within Afghanistan may prove counter-productive, radicalizing civilians. While little is certain, a modest degree of successful stability and reconstruction may be achieved by 2024 – most large cities and many small towns may be controlled by the Kabul government, official corruption may decline, and conceivably the country may integrate into a regional economy shared with Iran, Russia, China, and India.